1998
DOI: 10.1149/1.1838596
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Particle Generation during the Low‐Pressure Chemical Vapor Deposition of Borophosphosilicate Glass Films

Abstract: A particle beam mass spectrometer (PBMS) was used to monitor particle generation during the deposition of borophosphosilicate glass (BPSG) films in a Lam Research Corporation DSM 9800 low-pressure chemical vapor deposition reactor. The precursors used were tetraethylorthosilicate (TEOS), triethylborate (TEB), phosphine, and oxygen.Typical process pressures ranged from 1-3 Torr, while the process temperatures varied from 775-825°C. The PBMS monitored the flow in the reactor exhaust line, and under typical proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The absence of any emission from Si, B, P, and their relative chemical compound lines in the plasma is probably due to the low concentrations or the relatively low instrument sensitivities to these species. 16,17) However, the Si-O, B-O, and P=O bands existed in the FTIR spectra. Also from the XPS results, we confirmed that high percentage concentrations (at.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The absence of any emission from Si, B, P, and their relative chemical compound lines in the plasma is probably due to the low concentrations or the relatively low instrument sensitivities to these species. 16,17) However, the Si-O, B-O, and P=O bands existed in the FTIR spectra. Also from the XPS results, we confirmed that high percentage concentrations (at.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It was believed that the gas-phase nucleation would be harmful to the thin film growth. Gas phase-generated nanoparticles may cause killer defects, resulting in device failure, due to small feature sizes, which decrease to <100 nm [21]. However, Hwang and Lee [10] suggested that the deposition behavior of gas phase-generated nanoparticles differs drastically depending on whether they are electrically charged or not.…”
Section: Non-classical Crystallization 21 Theory Of Charged Nanoparmentioning
confidence: 99%
“…[4][5][6] However, the real-time measurement of nano-size particles formation according to the degree of thermal decomposition has not been studied yet. The particle beam mass spectrometer (PBMS) has proved to be effective in detecting particles generated thermal 8,9) and plasma enhanced 10) chemical vapor deposition (CVD) of thin films as a function of several deposition conditions. But conventional PBMS has a particle size overestimation problem, and then particle size measured by the PBMS was larger than the expected value because of an inappropriate gap width between the two deflection plates in the PBMS.…”
mentioning
confidence: 99%